The contributions of T cell-mediated immunity to protection from vaccine-preventable diseases: A primer - Janna R. Shapiro; Mario Corrado; Julie Perry; Tania H. Watts; Shelly Bolotin (Human Vaccines & Immunotherapeutics)
In the face of the ever-present burden of emerging and reemerging infectious diseases, there is a growing need to comprehensively assess individual- and population-level immunity to vaccine-preventable diseases (VPDs). Many of these efforts, however, focus exclusively on antibody-mediated immunity, ignoring the role of T cells. Aimed at clinicians, public health practioners, and others who play central roles in human vaccine research but do not have formal training in immunology, we review how vaccines against infectious diseases elicit T cell responses, what types of vaccines elicit T cell responses, and how T cell responses are measured. We then use examples to demonstrate six ways that T cells contribute to protection from VPD, including directly mediating protection, enabling antibody responses, reducing disease severity, increasing cross-reactivity, improving durability, and protecting special populations. We conclude with a discussion of challenges and solutions to more widespread consideration of T cell responses in clinical vaccinology.